Re-existing through memories and visions of the future. A futuring approach for multi-temporal, territoralised, heart-felt transition imaginaries - Mancusi,Simona (2025)
My main contribution to the Human Ecology field is exploring the relationship between memories and images of the future when pursuing transition imaginaries. By ‘feeling with the head and reasoning with the heart’, I used a sensory ethnographic method to listen to people's life stories during my fieldwork in Bolivia with territorial defenders. Throughout the data collection and analysis, there has been a strong focus on connecting to the stories through the heart and the body and giving particular importance to people's affections. During my data analysis, I attempted to corazonar my research process by creating altars in the form of a ritual, and reconnect with the memories from the fieldwork. Furthermore, through sketches and drawings, I attempted to visualise the territorial defenders' emerging imaginaries as a landscape of memories, everyday acts of re-existance and future anticipations. The aim was to reflect back and with the findings through theories, the heart, and a more democratic medium. The analysis shows a multi-temporal present where body-territories-memories and images of the future ignite re-existance practices, shaping everyday actions. Through this thesis, I am to offer an alternative mode of futuring. Rather than working on abstract or pre-designed images of the future, often colonised by progressive temporalities, I suggest working with future imaginaries by addressing people's materialities, involving affections, relations with the territories, memories and their everyday lives. My work offers human ecologists, transition designers and futurists a more embodied sentipensante futuring approach for cultivating transition imaginaries.
Keywords: futuring; transition design; imaginaries; transition; human ecology; memories; body territory; corazonamiento